1996
DOI: 10.1002/zaac.19966220514
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfonylamine. LXXII [1]. Triphenylcarbenium‐ und Triphenylphosphonium‐di(fluorsulfonyl)amid: Zwei Kristallstrukturen mit geordneten (FSO2)2N‐Lagen

Abstract: Reaktion von HN(SO2F)2 in CH2Cl2 mit Ph3P, Ph3PO oder Collidin (=B) ergibt die Verbindungen Ph3PH⊕[(FSO2)2N]⊖ (3), Ph3PO · HN(SO2F)2 und BH⊕ [(FSO2)2 · N]⊖ (7). Das durch Metathese von Ph3CBr mit [(C6H6)AgN · (SO2F)2] in CH2Cl2 erhältliche Carbeniumsalz Ph3C⊕ [(FSO2)2N]⊖ (5) kristallisiert aus Chloroform/Petrolether als Monosolvat Ph3C⊕ [(FSO2)2N]⊖ · CHCl3 (6). In Kombination mit einer sterisch gehinderten Base, z. B. Collidin, eignet sich 5 als Reagens für die Tritylierung schwach CH‐acider Moleküle (Beispiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In covalent R−N(SO 2 F) 2 derivatives, the S−O bond distances lie in the range 1.375−1.405 Å, which is close to the S−O bond length found in SO 2 F 2 (1.405 Å), where the S−O bond order is assigned as 2.0 by Gillespie et al These S−O distances are, however, shorter than the corresponding bond lengths found in CsN(SO 2 F) 2 [1.421(3) Å], , (C 6 H 5 ) 3 XN(SO 2 F) 2 [X = C, 1.414(3) Å; X = P, 1.419(2) Å], Me 3 PbN(SO 2 F) 2 [1.418(6) Å], NH 2 (SO 3 ) - (1.457 Å), , NH(SO 3 ) 2 2- [1.449 Å], , and N(SO 3 ) 3 3- (1.468 Å) . An increase in S−O bond order is observed in going from an ionic to a covalently bonded R−N(SO 2 F) 2 derivative.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In covalent R−N(SO 2 F) 2 derivatives, the S−O bond distances lie in the range 1.375−1.405 Å, which is close to the S−O bond length found in SO 2 F 2 (1.405 Å), where the S−O bond order is assigned as 2.0 by Gillespie et al These S−O distances are, however, shorter than the corresponding bond lengths found in CsN(SO 2 F) 2 [1.421(3) Å], , (C 6 H 5 ) 3 XN(SO 2 F) 2 [X = C, 1.414(3) Å; X = P, 1.419(2) Å], Me 3 PbN(SO 2 F) 2 [1.418(6) Å], NH 2 (SO 3 ) - (1.457 Å), , NH(SO 3 ) 2 2- [1.449 Å], , and N(SO 3 ) 3 3- (1.468 Å) . An increase in S−O bond order is observed in going from an ionic to a covalently bonded R−N(SO 2 F) 2 derivative.…”
Section: Resultssupporting
confidence: 73%
“…Although HN(SO 2 Cl) 2 and its derivatives have been known for over 3 decades, no structures with the N(SO 2 Cl) 2 moiety have been reported . There has been a recent increase in interest in the structures of compounds containing the N(SO 2 X) 2 moiety. ,,,, The modifications we have made to the synthetic procedure for the preparation of HN(SO 2 F) 2 afford this acid, as well as its fluorinated analogue in high purity. The availability of diffraction quality crystals formed at low temperatures for these acids and CF 3 CH 2 N(SO 2 F) 2 provided an opportunity to study the cryogenic crystal and molecular structures of these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the perchlorate anion O-Cl-O angles lie in the range 106.03 (18)-113.0 (4) . The P-H distance of 1.25 (5) Å in (I) is comparable to that in [Ph 3 PH] 2 [SnCl 6 ] [1.285 (3) Å ; Yatsenko et al, 1986], Hiemisch et al, 1996], but shorter than that in [Ph 3 PH]Br [1.61 (9) Å ] where the proton is directed towards the bromide anion (Bricklebank et al, 1993). The molecular structure of (I), showing the atom-numbering scheme, and with displacement ellipsoids at the 50% probability level for non-H atoms.…”
mentioning
confidence: 53%
“…Tabulation of all data available at this time suggests that the degree of N---C bond lengthening in N-alkyl disulfonylamines correlates with the stability order of the carbocations derived from the N-alkyl groups. Corroborative evidence is seen in the related trityl compound Ph3C+-N(SO2F)2, which is purely ionic in the solid state (Hiemisch et al, 1996). N-Organyl disulfonylamines, including (I)-(III), generally display a nearly planar central grouping formed by the N, C and two S atoms bonded to it.…”
Section: Commentmentioning
confidence: 98%